2016
DOI: 10.1063/1.4945691
|View full text |Cite
|
Sign up to set email alerts
|

A continuous dry 300 mK cooler for THz sensing applications

Abstract: We describe and demonstrate the automated operation of a novel cryostat design that is capable of maintaining an unloaded base temperature of less than 300 mK continuously, without the need to recycle the gases within the final cold head, as is the case for conventional single shot sorption pumped (3)He cooling systems. This closed dry system uses only 5 l of (3)He gas, making this an economical alternative to traditional systems where a long hold time is required. During testing, a temperature of 365 mK was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Finally, a miniature dilution refrigerator (MDR) is used to cool the focal plane to ∼ 130 mK. It should be noted that while the CC7 stage runs continuously at a much higher temperature than the performance reported by Klemencic et al, 12 this is due to operating under a substantial thermal load, approximately 650 µW, which is due to thermal loading from the 4 K and 1 K stages and also from heating the 3 He evaporator of the miniature dilution refrigerator.…”
Section: Instrument Designmentioning
confidence: 99%
“…Finally, a miniature dilution refrigerator (MDR) is used to cool the focal plane to ∼ 130 mK. It should be noted that while the CC7 stage runs continuously at a much higher temperature than the performance reported by Klemencic et al, 12 this is due to operating under a substantial thermal load, approximately 650 µW, which is due to thermal loading from the 4 K and 1 K stages and also from heating the 3 He evaporator of the miniature dilution refrigerator.…”
Section: Instrument Designmentioning
confidence: 99%
“…The performance of a similar system has been described previously and has been shown to operate at a temperature of 300 mK under minimal thermal loading and to be thermally stable for in excess of three months. 2 Our system is expected to operate at a higher temperature due to the presence of a higher thermal load, as described later. The temperature at the final head of the CS cooler fluctuates naturally during its operation due to the constant recycling of the system.…”
Section: Cooling Chainmentioning
confidence: 99%
“…It has been shown that through PID control of a heater mounted to this head, the achieved temperature can be stabilised at 365.0 ± 0.1 mK in the presence of a 20-µW thermal load (designed to represented the device load for a particular application). 2 PID control of these units is not required for MUSCAT as the final cooler provides sufficient thermal dampening to nullify the oscillations at the detector. In order to operate at the levels of thermal loading anticipated for MUSCAT, the timing and pump temperatures used to cycle each subsystem have been tuned to ensure that the system being regenerated is fully prepared prior to the liquid He 3 being depleted in the other system.…”
Section: Cooling Chainmentioning
confidence: 99%
“…In these two cases, the low energy involved makes infrared (IR) and terahertz (THz) spectroscopies well suited to probe these excitations [1,2]. The control of the temperature is also important to characterize the optical properties of detectors having an interest for astronomical applications [3][4][5]. Indeed, in many space missions, the detector must be cooled down to sub-Kelvin temperature in order to reduce significantly the thermal noise, essential to study the universe background radiation or low intensity THz sources.…”
Section: Introductionmentioning
confidence: 99%
“…To reach this sub-Kelvin temperature range on a material, two methods are commonly employed: dilution of 3 He in 4 He [3][4][5] or adiabatic demagnetization refrigerators (ADR) using paramagnetic salts [6,7]. For condensed matter studies developed on the AILES Beamline of Synchrotron SOLEIL (an open access facility [8]) the samples are usually in the mm 3 scale due to the complex chemical or physical syntheses.…”
Section: Introductionmentioning
confidence: 99%